Improving Fourth-Grade Students' Learning Outcomes Using the Discovery Learning Method in Indonesian at SD Negeri 200111 Padangsidimpuan - Darinda Sofia Tanjung; Juliana; Dyan Wulan Sari HS (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of students' learning outcomes in Indonesian through the use of the discovery learning method on the reading text and topic sentence subject matter in class IV at SD Negeri 200111 Padangsidimpuan. This classroom action research consists of 2 cycles with the research subjects of all 26 fourth-grade students, which consisted of 9 male and 17 female students. Data collection techniques were observation of teacher and student activities and student learning outcomes tests. Data analysis used quantitative and descriptive qualitative analyses by determining the average percentage of teacher and student activity, the completeness of student learning outcomes, and then determining the success criteria. Based on the data analysis results, it is concluded that there was an improvement of Indonesian students' learning outcomes on the reading and topic sentence subject matters. It can be seen from the percentage of classical learning completeness in cycle I, there were 17 female students or 65.39% of 26 students and 9 male students or 34.61% of 26 students. While in cycle II there was an increase where there were 23 students or 88.5% who completed from 26 students and 3 students or 11.5% who did not complete from 26.